Math
posted by Yoli .
sqrt of 450 simplified with solution

Math 
Catherine
Simplify the radical by breaking the radicand up into a product of known factors.
Exact Form:
15
√
2
15
2
Decimal Form:
21.21320343
Respond to this Question
Similar Questions

Inequality
When I solve the inquality 2x^2  6 < 0, I get x < + or  sqrt(3) So how do I write the solution? 
Math Help please!!
Could someone show me how to solve these problems step by step.... I am confused on how to fully break this down to simpliest terms sqrt 3 * sqrt 15= sqrt 6 * sqrt 8 = sqrt 20 * sqrt 5 = since both terms are sqrt , you can combine … 
math
What is the square root of 80 in simplified radical form? 
Calculus
Please look at my work below: Solve the initialvalue problem. y'' + 4y' + 6y = 0 , y(0) = 2 , y'(0) = 4 r^2+4r+6=0, r=(16 +/ Sqrt(4^24(1)(6)))/2(1) r=(16 +/ Sqrt(8)) r=8 +/ Sqrt(2)*i, alpha=8, Beta=Sqrt(2) y(0)=2, e^(8*0)*(c1*cos(0)+c2*sin(0))=c2=2 … 
PreCalcPlease check my answerI think its correc
Could someone please check theseI had tried one last night but it was really wrong so I'm been workinghopefully these are correct. What are the roots of the equation and answers have to be simplified 2x^2 + 5x10 =0 2x^2 + 5x10+10=0+10 … 
PreCalcPlease check my answerI think I have it
Could someone please check theseI had tried one last night but it was really wrong so I'm been workinghopefully these are correct. What are the roots of the equation and answers have to be simplified 2x^2 + 5x10 =0 2x^2 + 5x10+10=0+10 … 
PreCalcPlease check my answerI think I have it
Could someone please check theseI had tried one last night but it was really wrong so I'm been workinghopefully these are correct. What are the roots of the equation and answers have to be simplified 2x^2 + 5x10 =0 2x^2 + 5x10+10=0+10 … 
PreCalc
Could someone please check theseI had tried one last night but it was really wrong so I'm been workinghopefully these are correct. What are the roots of the equation and answers have to be simplified 2x^2 + 5x10 =0 2x^2 + 5x10+10=0+10 … 
Math (Algebraic Proving)
Show that the equation sqrt((xc)^2 + y^2)+sqrt((x+c)^2 + y^2) = 2a can be simplified to (x^2/a^2) + (y^2/b^2) = 1 where b^2 = a^2c^2. 
Algebra
Which of these expressions is in simplified form?